Penerapan Arsitektur Healing Therapeutik pada Perancangan Pet Center di Kota Makassar - Aras, Adnan Mustadjab; Amin, Burhanuddin; Sam, Mukhlishah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2025)
The Pet Center in Makassar City offers a solution to the growing need for interaction between pets and their owners, considering the high interest in pet ownership and the development of pet enthusiast communities. However, there is currently no adequate facility that allows pets to walk or gather in an environment that is friendly to both humans and animals, creating the need for a pet- and human-friendly space. This pet center is designed to facilitate comfortable and safe human-pet interactions. The design process incorporates an analysis of animal behavioral characteristics, which is integrated into the design concept to tailor the space to reflect traits such as activity, curiosity, and friendly, playful personalities of pets. The